2023
DOI: 10.1021/acsmaterialslett.3c00068
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Effect Triggered by π–π Interactions in a Flexible Terpyridine Metal–Organic Framework

Abstract: Shape-memory polymers and alloys are adaptable materials capable of reversing from a deformed, metastable phase to an energetically favored original phase in response to external stimuli. In the context of metal− organic frameworks, the term shape-memory is defined as the property of a switchable framework to stabilize the reopened pore phase after the first switching transition. Herein we describe a novel flexible terpyridine MOF which, upon desolvation, transforms into a nonporous structure that reopens into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although the same effect was reported for a metal–organic framework (MOF) in 2013, [6] the second example involving a MOF was only reported in 2018 [12] . Since then only a handful of additional articles have described similar observations for MOFs [13–18] …”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although the same effect was reported for a metal–organic framework (MOF) in 2013, [6] the second example involving a MOF was only reported in 2018 [12] . Since then only a handful of additional articles have described similar observations for MOFs [13–18] …”
Section: Introductionmentioning
confidence: 70%
“…[12] Since then only a handful of additional articles have described similar observations for MOFs. [13][14][15][16][17][18] From the various structure-property studies by the groups of Atwood [10] and Ripmeester [19] it is possible to construct a partial phase interconversion scheme for TBC4 based on the two stimuli of CO 2 gas pressure and heat (Text S2). However, some of the aspects of this scheme are conflicting owing to the lack of conclusive in situ experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, should FMOMs exhibit structural transformations between polymorphic phases, then they could also function as SMMs (Scheme 1). Indeed, recent studies have demonstrated the SME in a handful of 3D FMOMs, 41–47 as evidenced by their successive sorption isotherms. Despite these encouraging findings, the SME remains an underexplored phenomenon in molecular FMOMs, with only one known example, a platinum( ii )–diimine complex that was studied for its vapochromic shape-memory characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…23 In the field of structural phase transitions, metal−organic frameworks (MOFs) have drawn significant attention. The flexibility inherent to some MOFs 24,25 allows them to undergo structural changes when exposed to a variety of external stimuli such as temperature, 26,27 pressure, 28−30 presence of guest molecules, 31,32 or electric field. 33,34 Notably, these structural changes have the potential to alter the key characteristics of MOFs and have been proved advantageous, as they may improve adsorption-related applications such as separation and catalysis, 35−37 or contribute to mechanical energy storage and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of structural phase transitions, metal–organic frameworks (MOFs) have drawn significant attention. The flexibility inherent to some MOFs , allows them to undergo structural changes when exposed to a variety of external stimuli such as temperature, , pressure, presence of guest molecules, , or electric field. , Notably, these structural changes have the potential to alter the key characteristics of MOFs and have been proved advantageous, as they may improve adsorption-related applications such as separation and catalysis, or contribute to mechanical energy storage and absorption. , Numerous studies have explored the relationship between structural changes and individual phonon modes and their groups. Ryder et al performed a comprehensive experimental and theoretical analysis of vibrational modes in three zeolitic imidazolate frameworks (ZIFs): ZIF-4, ZIF-7, and ZIF-8 .…”
Section: Introductionmentioning
confidence: 99%